الأخلاق بين النظري و التطبيقى عند طه عبد الرحمان - قانه,مسعود; الخذير,لحسن (University of Eloued جامعة الوادي, 2024)
مما لاشك فيه أن الأخلاق احتلت مكانة واهتمام كبير لدى الفلاسفة والمفكرين عبر العصور بغرض ضبط ماهيتها وتفسيرها, حيث تعددت المذاهب الأخلاقية تبعا لذلك، بالنظر إلى الأخلاق كدراسة معيارية للخير والشر، ولعل من ابرز تمفصلها الأخلاق النظرية والأخلاق التطبيقية, ومن الذين خاضوا في هذا الموضوع المفكر طه عبد الرحمن في ظل نقد الفلسفة الأخلاقية الغربية والتركيز على طرح بديل يتمثل في الحداثة الإسلامية المعاصرة, حيث يرفض الفصل بين الأخلاق النظرية والتطبيقية كما ينتقد العقل المجرد مركزاً على البعد الروحي والتطبيقي الذي يؤثر على الأفراد والمجتمعات, من خلال تأسيس الأخلاقية على مفهوم التخلق ببعده الروحي , وهي جوهر الفعل الإنساني,بتكامل التنظير الاخلاقي بالتطبيق العملي دون انفصال. Summary: There is no doubt that ethics has occupied a significant place and gained great attention among philosophers and thinkers throughout history in an attempt to define and interpret its essence. Ethical schools have varied accordingly, considering ethics as a normative study of good and evil. Among its key branches are theoretical and applied ethics. One of the prominent thinkers in this field is Taha Abderrahman, who critically examines Western moral philosophy and advocates for an alternative approach based on contemporary Islamic modernity. He rejects the separation between theoretical and applied ethics and critiques pure reason, emphasizing the spiritual and practical dimensions that influence individuals and societies. His ethical foundation is built on the concept of moral embodiment with its spiritual depth, which he considers the core of human action, integrating ethical theorization with practical application without separation.
Keywords: ، الأخلاق النظرية; الأخلاق التطبيقية; الحداثة الغربية; الحداثة الاسلامية المعاصرة